Gender Relations in the Modern Family: A Sociological Study of Changing Domestic and Public Roles - Tri amanda (Generasi Sains Indonesia, 2025)
This study examines the dynamics of gender relations in modern Indonesian families, focusing on the transformation of domestic and public roles. Using a quantitative survey method involving 700 respondents (350 couples) from five major cities, data were collected through Likert-scale questionnaires and analyzed using descriptive statistics, Pearson correlations, and multiple linear regression. The findings reveal that child-rearing is increasingly perceived as a shared responsibility, yet domestic work remains disproportionately borne by women, reflecting the persistence of the double burden. At the same time, women’s economic contributions are widely acknowledged as essential, although men continue to be regarded as the primary breadwinners, illustrating a form of patriarchal bargain. Regression analysis shows that public role participation (β = 0.41) has a stronger influence than domestic role participation (β = 0.33) on perceptions of gender equality, suggesting that women’s involvement in the public sphere plays a key role in reshaping family relations. However, the persistence of traditional norms indicates that gender equality in modern families remains more aspirational than fully realized. Overall, the study concludes that gender relations in Indonesian modern families represent a negotiated balance between traditional patriarchal values and emerging egalitarian ideals.